Upper bounds for E-J matrices - Akgun, F. Aydin; Rhoades, B. E. (NATURAL SCIENCES PUBLISHING CORPORATION, 2012)
In a recent paper [5] Lashkaripour and Foroutannia obtained the norm of a Hausdorff matrix, considered as a bounded linear operator from l(p)(w) to l(p)(v), where l(p)(w) and l(p)(v) are weighted l(p)-spaces, and p >= 1. As a corollary to this result they obtain a new proof for a Hausdorff matrix, with nonnegative entries, to be a bounded operator on l(p) for p > 1. In this paper these results are extended to the Endl- Jakimovski (E-J) generalized Hausdorff matrices.
Keywords: nonnegative decreasing sequences; E-J generalized Hausdorff matrices; upper bounds; HAUSDORFF MATRICES; OPERATORS; LP; Mathematics; Physics